Analisis Pengaruh Distribusi Hujan Rancangan Terhadap Karakteristik Genangan Pada Sistem Drainase Kalibokor, Kota Surabaya - Aulia Putri Yelisa; Umboro Lasminto (AGREGAT, 2026)
The Kalibokor drainage system in Surabaya is one of the areas frequently affected by inundation during the rainy season, owing to the limited capacity of its channels to accommodate surface runoff. This condition is further aggravated by the high rainfall intensity characteristic of urban areas, which increases runoff discharge and the potential for flooding. Variations in the temporal distribution of design rainfall can produce different hydrological responses within the drainage system, thereby potentially influencing inundation characteristics in terms of flooded area and inundation depth. This study aims to analyze the effect of rainfall distribution design on the inundation area and depth within the Kalibokor drainage system, Surabaya. The method employed is two-dimensional hydraulic modeling using HEC-RAS 2D with a rain-on-grid approach to spatially simulate overland flow and inundation. The model was calibrated against the existing inundation conditions before the simulation. Simulations were carried out using a rainfall design with a 10-year return period and six duration variations ranging from 1 to 6 h. The simulation results indicate that rainfall duration variation affects the inundation characteristics within the study area. The largest inundation area occurred at a rainfall duration of 1 h, covering approximately 6.113 km², while at a duration of 6 hours the inundation area decreased to approximately 5.592 km². The Inundation formed across all scenarios was predominantly characterized by depths of less than 0.10 m, accounting for more than 50% of the total inundation area. The results demonstrate that shorter rainfall durations tend to produce larger and deeper inundation extents, whereas increasing rainfall duration reduces both the inundation area and depth within the Kalibokor drainage system. These findings indicate that rainfall distribution has a significant influence on flood inundation response and should be considered consideration in the evaluation and planning of urban drainage systems to improve channel capacity in conveying stormwater runoff.